Clinical application of bladder MRI and the Vesical Imaging-Reporting and Data System - Panebianco, Valeria; Briganti, Alberto; Boellaard, Thierry N; Catto, James; Comperat, Eva; Efstathiou, Jason; van der Heijden, Antoine G; Giannarini, Gianluca; Girometti, Rossano; Mertens, Laura; Takeuchi, Mitsuru; Muglia, Valdair F; et al. (Nature reviews. Urology, 2024)
Diagnostic work-up and risk stratification in patients with bladder cancer before and after treatment must be refined to optimize management and improve outcomes. MRI has been suggested as a non-invasive technique for bladder cancer staging and assessment of response to systemic therapy. The Vesical Imaging-Reporting And Data System (VI-RADS) was developed to standardize bladder MRI image acquisition, interpretation and reporting and enables accurate prediction of muscle-wall invasion of bladder cancer. MRI is available in many centres but is not yet recommended as a first-line test for bladder cancer owing to a lack of high-quality evidence. Consensus-based evidence on the use of MRI-VI-RADS for bladder cancer care is needed to serve as a benchmark for formulating guidelines and research agendas until further evidence from randomized trials becomes available.
Keywords: nádory močového měchýře; výzkumný projekt; Consensus; močový měchýř; Humans; Magnetic Resonance Imaging; retrospektivní studie; lidé; Urinary Bladder Neoplasms; Retrospective Studies; Research Design; magnetická rezonanční tomografie; Urinary Bladder; konsensus